EVALUATION RESULTS ON FACTORS AFFECTING REGIONAL LINKAGE IN AN GIANG TOURISM DEVELOPMENT FROM A GEOGRAPHICAL PERSPECTIVE - To Minh CHAU (Geo Journal of Tourism and Geosites)
This study was conducted in An Giang province, Vietnam, aiming to examine the variables and explain the factors affecting the tourism development of An Giang province in regional linkages from a geographical perspective. This research employed a non-probability sampling method with 300 visitors by distributing a survey. The data gathered from the survey was encoded and processed using SPSS version 29.0. Pearson correlation was used in this study to investigate the relationship between factors of natural tourism resources, cultural tourism resources, infrastructure, safety in tourism, and tourism policy with the tourism development of An Giang province in regional linkages. The results showed that factors of cultural tourism resources and natural tourism resources have a high correlation with regional linkages in tourism development; factors of infrastructure and tourism safety with regional linkages in tourism development have a medium correlation; tourism development policy factors have a low correlation but are worth considering with regional linkages in tourism development.